Building the entrepreneurial state: A new framework for envisioning and evaluating a mission-oriented public sector - Mariana Mazzucato (Levy Economics Institute of Bard College, 2015)
Today, countries around the world are seeking "smart" innovation-led growth, and hoping that this growth is also more "inclusive" and "sustainable" than in the past. This paper argues that such a feat requires rethinking the role of government and public policy in the economy - not only funding the "rate" of innovation, but also envisioning its "direction." It requires a new justification of government intervention that goes beyond the usual one of "fixing market failures." It also requires the shaping and creating of markets. And to render such growth more "inclusive," it requires attention to the ensuing distribution of "risks and rewards." To approach the innovation challenge of the future, we must redirect the discussion, away from the worry about "picking winners" and "crowding out" toward four key questions for the future: 1. Directions: how can public policy be understood in terms of setting the direction and route of change; that is, shaping and creating markets rather than just fixing them? What can be learned from the ways in which directions were set in the past, and how can we stimulate more democratic debate about such directionality? 2. Evaluation: how can an alternative conceptualization of the role of the public sector in the economy (alternative to MFT) translate into new indicators and assessment tools for evaluating public policies beyond the microeconomic cost/benefit analysis? How does this alter the crowding in/out narrative? 3. Organizational change: how should public organizations be structured so they accommodate the risk-taking and explorative capacity, and the capabilities needed to envision and manage contemporary challenges? 4. Risks and Rewards: how can this alternative conceptualization be implemented so that it frames investment tools so that they not only socialize risk, but also have the potential to socialize the rewards that enable "smart growth" to also be "inclusive growth"?
Keywords: L1; L5; O38; O25; 330; Finance; Industrial Policy; Mission-oriented Innovation